S-Quinolin-2-ylmethyldithiocarbazate - How, Fiona Ni Foong; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
In the title compound, C11H11N2S2, there is an intramolecular N—H N [2.778 (2) A ° ] hydrogen bond linking the quinoline N atom and the imino N atom. The planar quinoline ring system forms an angle of 67.7 (1) with the dithiocarbazate group. Bond angles for both S—C—S [115.66 (8)] and N—C—S [119.05 (11)] are comparable with cis–trans S-methyldithiocarbazate but differ from those found in trans–cis Smethyldithiocarbazate and trans–cis S-benzyldithiocarbazate.This is due to the N—H N hydrogen bond that exists only in the cis–trans conformation found for the title compound.